2018
DOI: 10.4236/me.2018.91004
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Economics in the Era of One Belt One Road and Counter-Globalization

Abstract: After an overview of spatial economics, we review China's recent One Belt One Road (OBOR) Initiative, and the contrary counter-globalization forces in the contemporaneous geopolitical and social landscapes. We then discuss their impact on and new paradigms in spatial economics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…China possesses both the financial resources of more than US $3.5 trillion in foreign exchange reserves and a vast experience in infrastructural development. Therefore, BRI promises massive infrastructural development that provides the bases for economic and industrial prosperity in the region [55]. BRI-related projects involve 70% of the global population, 75% of its known energy reserves and territory, 25% of global trade, and 55% of global GDP [49].…”
Section: An Overview Of the Belt And Road Initiativementioning
confidence: 99%
“…China possesses both the financial resources of more than US $3.5 trillion in foreign exchange reserves and a vast experience in infrastructural development. Therefore, BRI promises massive infrastructural development that provides the bases for economic and industrial prosperity in the region [55]. BRI-related projects involve 70% of the global population, 75% of its known energy reserves and territory, 25% of global trade, and 55% of global GDP [49].…”
Section: An Overview Of the Belt And Road Initiativementioning
confidence: 99%
“…With more than US$ 3.5 trillion in foreign-exchange reserves, China has rich experience in financial capital and infrastructure development. The "Belt and Road" initiative thus promises the development of large-scale infrastructure, laying the cornerstone for economic and industrial affluence in the Region (Lai, T. L., Tang, J., & Yin, H. 2018). Projects linked to the 'Belt and Road' initiative comprise 70 % of the world's population, 75% of known oil, reserves and territories, 25% of global trade, and 55% of global GDP (Khan, M. K. et al, 2018).…”
Section: Bri Overviewmentioning
confidence: 99%
“…In addition, theoretically, a few studies have investigated the overall impact of BRI on the economic development of all countries along the routes. Lai et al (2018) illustrated that BRI can build a cohesive spatial economic network integrating the multinational region on China's unique experience with its economic development and free trade zones. Silin et al (2018) found that the mutual benefit within the framework of BRI involves mainly international cooperation based on mutual benefits for all participants, the promotion of economic growth and welfare, and the development of modern infrastructure through joint investment.…”
Section: Introductionmentioning
confidence: 99%